EDUKASI PEMAHAMAN IMBUHAN PADA SISWA SEKOLAH DASAR GUNA MENINGKATKAN KEMAMPUAN BERBAHASA INDONESIA - Jasmine, Yusticia; Haikal, Muhammad Dava; Ernawati, Surni; Febrian, Alvin; Nirmala, Syahda; Mislan, Mislan; Dewi, Irma Nurmala (Jurnal Pengabdian Indonesia (JPI), 2025)
Parents, especially mothers, have taught the ability to speak good and correct Indonesian since early childhood. However, many still do not understand affixes in Indonesian vocabulary. In the school environment, Indonesian is a mandatory subject that students must study at every grade level in elementary school. Affixes in a sentence can provide and change the meaning and function of the sentence and the type of sentence itself. Affixes are used and adjusted to the sentences or specific paragraphs used. The purpose of the community service conducted by the KKM 41group students of Universitas Bina Bangsa, is to convey the knowledge they have acquired at the campus. The method used in this service is to educate elementary school students about affixes to improve their Indonesian language skills. The result of this service is that the students have a better understanding of learning affixes and practice directly by taking a test to assess their knowledge, with the test results being excellent.